2018
DOI: 10.14738/abr.63.4075
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Talent Management on the Success of Organization Development

Abstract: This study is done to find the effect of talent management on organization success. The finding of the study is that the effective talent management does result in the success or development of organization. In this study, organization development is divided into two boarder categories, which are positive or negative growth of organization. Positive growth of Organization development was done by recruitment and selection, training and development whereas negative variables are considered employee retention, sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 1 publication
0
13
1
Order By: Relevance
“…Several studies suggested effective use of talent management practices for desirable organizational outcomes such as employee retention (Abdollahbeigi et al, 2017) psychological attachment between employees and organization (Asrar, 2018), job satisfaction, motivation and commitment (Chen, 2004). Few others found it as a predictor of effective human capital (Ghorbanhosseini, 2013), employee innovative performance (Orth, 2017), employee engagement and so on.…”
Section: R M B Rmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies suggested effective use of talent management practices for desirable organizational outcomes such as employee retention (Abdollahbeigi et al, 2017) psychological attachment between employees and organization (Asrar, 2018), job satisfaction, motivation and commitment (Chen, 2004). Few others found it as a predictor of effective human capital (Ghorbanhosseini, 2013), employee innovative performance (Orth, 2017), employee engagement and so on.…”
Section: R M B Rmentioning
confidence: 99%
“…The C.I.P.D. Institute finds creativity to be a diverse mix of talents, intelligence, social capabilities and high ability (Asrar, 2018;Bethke et al, 2011). Talent is the product of the organizational movement of individuals, how they join the organisation, how they grow their abilities that activate the actions of subordinates to perform their duties innovatively within the organization (Rodrigues, 2019;Tai, 2016;Battistelli et al, 2014…”
Section: Literature Review Talent Management Practice (Tmp) Employeementioning
confidence: 99%
See 1 more Smart Citation
“…This is aimed at not only retaining the employees but also enjoying increased productivity and capability, better linkage between individual's efforts and organizational goals, commitment of valued employees as well as reduced turnover, increased bench strength and a better fit between people's jobs and skills. Asrar, Azhar, and Hussain (2018) posit that employee retention has an effect on organization's success. This is due to the reduction in employee turnover, increase in employee motivation and commitment to the organization following the employee's satisfaction with the job and general stability that an organization enjoys when they are able to retain their talented employees.…”
Section: Talent Development and Organizational Effectivenessmentioning
confidence: 99%
“…Employ retention has an effect on organization's success (Asrar et al, 2018). To guarantee effective leadership for the future, organizations endeavor to attract and retain top talent (Govaerts et al, 2011).…”
Section: Talent Maintenancementioning
confidence: 99%